Topical studied on subgrid-scale dynamic processes in stably stratified geophysical flows in polar regions - Urbancic, Gabin (Helsingin yliopisto, 2024)
The most significant changes in climate are observed in the Arctic, which is estimated to be warming at rates two to four times faster than the global average. In Antarctica, sea ice extent is experiencing a rapid decline, even faster than the decline observed in the Arctic. Therefore, the polar regions are highly vulnerable to the warming climate. To improve the ability of climate models to represent polar regions, a better understanding of critical physical processes is needed. This thesis focuses on the study of two subgrid-scale dynamic processes important to polar climate: submeso-scale motions in the atmospheric surface layer and internal waves in the Arctic ocean. Submeso-scale motions are important in the atmospheric surface layer during stable conditions, a common situation in polar regions due to the often negative radiative energy balance at the surface. The stable stratification creates a wave-guide for various modes of motion, each with different forcing mechanisms and properties, and each interacting uniquely with turbulence and mixing. The complexity of these motions makes the problem intractable to classical theoretical approaches. In this thesis, a novel method using autocorrelation functions is developed to characterize the occurrence and timescales of submeso-scale motions. Additionally, case study work is performed to improve the understanding of how observed submeso-scale motions interact with turbulence. Internal waves in the Arctic Ocean provide the energy needed to mix the warm Atlantic water below up to the surface, influencing the growth and melt of sea ice. This thesis addresses the dynamics and behavior of internal waves generated by tides in the region near the Yermak Plateau, a critical area as it is the last barrier before warm Atlantic water enters the Arctic Ocean. Mechanisms for internal wave propagation are demonstrated for both diurnal and semi-diurnal tides, and the conditions for the generation of internal solitary waves, which induce strong local mixing events, are ...